Analyzing the Mediating Role of Food Insecurity between Economic Factors and Child Health in Pakistan: An Application of Haye’s Logistic Model - Abdul Mansoor; Dr. Sabahat Subhan (Journal of Management Practices, Humanities and Social Sciences, 2022)
This study tends to assess the critical selected economic factors intervening the child health problems in Pakistan. Child health problem is of great concern and became even more important after the United Nation’s Sustainable Development Goals vision of Global Social, Economics, and Environmental sustainability. This study analyses the data of the Pakistan Household Integrated Economic Survey (HIES) 2018-19, which is the latest available data in the current year, 2022. A total frequency of 24809 households are included in the study sample and are inquired about their economic proceeding of life and their child's health problems. Child health is a derived factor that is not obviously directly affected by its socio-economic determinants. Unlike the previous studies, this study follows an indirect analysis while explaining child health determinants. Hayes' process of mediation is applied to see the role of global food insecurity in the households in the country and its implication on the child health ratio in Pakistan. This study implies a significant negative role in asset poverty. Food insecurity on the child health in Pakistan, meaning that if a household is food insecure, that will lead to a high risk of child adverse health problems and vice-versa. Moreover, there are some direct effects of asset poverty on the child's health as they assess the fiat source of finance for the household after a liquid form of monetary assets.